Implementation of Internal Policy Head of Madrasah In Improving The Quality of Learning - Amirudin, Ja’far; Supiana; Zaqiah, Qiqi Yuliati; Rohimah, Elis (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This research endeavors to elucidate the execution of internal policies by the school principal to enhance educational standards. Employing a qualitative method with a descriptive approach, the study reveals that the madrasa head, vested with the responsibility of guiding the educational institution, holds a pivotal role in shaping its trajectory. Indeed, the effectiveness of the madrasa, particularly in terms of elevating educational quality, significantly hinges upon the leadership of the head. Various endeavors are undertaken to enhance educational quality, encompassing initiatives such as reinforcing teacher discipline, augmenting pedagogical knowledge, and providing coaching for teacher performance improvement. Additionally, efforts to elevate student standards include mentorship and ensuring the provision of necessary infrastructure conducive to learning. These measures are integral to fulfilling the role of nurturing the students' academic growth effectively.